2020
DOI: 10.7717/peerj.8844
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ammonia oxidizers and denitrifiers in response to compost addition in black soil, Northeast China

Abstract: Organic fertilizer application could have an impact on the nitrogen cycle mediated by microorganisms in arable soils. However, the dynamics of soil ammonia oxidizers and denitrifiers in response to compost addition are less understood. In this study, we examined the effect of four compost application rates (0, 11.25, 22.5 and 45 t/ha) on soil ammonia oxidizers and denitrifiers at soybean seedling, flowering and mature stage in a field experiment in Northeast China. As revealed by quantitative PCR, compost addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…In this regard, the application of compost amendments into soil has been shown to increase network complexity for both bacteria and fungi when compared to inorganic fertilization and/or unamended treatments [100][101][102][103]. A similar trend in co-occurrence networks has been reported for other types of amendments like manure and straw [104].…”
Section: Features Of Microbial Co-occurrence Network In Compost-and Digestate-amended Soilssupporting
confidence: 53%
See 1 more Smart Citation
“…In this regard, the application of compost amendments into soil has been shown to increase network complexity for both bacteria and fungi when compared to inorganic fertilization and/or unamended treatments [100][101][102][103]. A similar trend in co-occurrence networks has been reported for other types of amendments like manure and straw [104].…”
Section: Features Of Microbial Co-occurrence Network In Compost-and Digestate-amended Soilssupporting
confidence: 53%
“…Particular emphasis has been placed on microbial groups that carry out key functions in the agroecosystems, namely, those affecting nitrogen turnover rates. Yang et al [100] observed that the complexity of both ammonia oxidizers and nirS containing denitrifiers networks gradually increased along with the compost rate. This is of particular importance for the productivity of plants given that nitrification and denitrification are among the most important soil N transformations.…”
Section: Features Of Microbial Co-occurrence Network In Compost-and Digestate-amended Soilsmentioning
confidence: 99%
“…Thus, in the high-B treatment, the functionalities predicted from 16S rRNA gene sequencing (using FAPROTAX) indicated greater potential denitrification and lower potential nitrification and aerobic ammonia oxidation, together potentially resulting in high levels of NH4 + in soil. Other studies have shown that compost addition can increase the rate of denitrification relative to nitrification (Yang et al, 2020;Yin et al, 2019). This potential release of NH4 + in soil links with the known ability of these soluble chemical forms in soil to dissolve minerals, via chelation, and to promote their solubility in the soil solution and hence their acquisition by plants and microbes (Adeleke et al, 2017;Antoniadis and Alloway, 2002).…”
Section: Boron Impacts On the Soil Chemistry And Plant Physiologymentioning
confidence: 95%
“…After that, we built a neighbor-joining tree using a Kimura 2-parameter distance with 1000 bootstrap replicates in MEGA 6 [41] to classify AOA-AOB OTUs. We used the nomenclature for AOA-amoA clusters as defined by [42] and the nomenclature for AOB-amoA as defined by [23]. The sequences of AOA-amoA and AOB-amoA were deposited in the NCBI database (Accession number: PRJNA723364 and PRJNA722852).…”
Section: High-throughput Sequencing and Bioinformatic Analysismentioning
confidence: 99%
“…More experimental evidence is needed, especially to confirm competitive interaction with keystone taxa in microbial networks. Some studies have been conducted to explore the effects of chemical and organic fertilizers on bacterial communities to discover taxonomic composition and phylogenetic diversity and its environmental drivers [1,8,23,24]. Though this knowledge is crucial in understanding soil microbial diversity, there is still the need to study the long-term effects of different fertilization regimes in the semi-arid Loess Plateau of northwestern China, where soil fertility loss and climate change are of major concern [25].…”
Section: Introductionmentioning
confidence: 99%